2007
DOI: 10.1161/strokeaha.107.488395
|View full text |Cite
|
Sign up to set email alerts
|

Probable Migraine With Visual Aura and Risk of Ischemic Stroke

Abstract: Background and Purpose-Migraine with aura is associated with ischemic stroke, but few studies have investigated the clinical and anatomic features of this association. We assessed the association of probable migraine with and without visual aura with ischemic stroke within subgroups defined by stroke subtype, vascular territory, probable migraine characteristics, and other clinical features. Methods-Using data from a population-based, case-control study, we studied 386 women ages 15 to 49 years with first isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
295
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(315 citation statements)
references
References 40 publications
11
295
0
9
Order By: Relevance
“…A recent Icelandic cohort study of midlife migraineurs also has shown that female MA is correlated with latelife cerebellar infarct-like lesions on magnetic resonance imaging [13]. Causative mechanism of those vascular disorders might contribute to prothrombotic actions, CVD risk factors, vascular reactivity, specific gene variants, congenital heart diseases, migraine attack frequency, migrainespecific treatment and pathophysiological involvements of the migraine [5,9,[14][15][16]. Major prospective studies evaluated CVD risk factors in large number of migraineurs and non-migraineurs [10,13,17,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Icelandic cohort study of midlife migraineurs also has shown that female MA is correlated with latelife cerebellar infarct-like lesions on magnetic resonance imaging [13]. Causative mechanism of those vascular disorders might contribute to prothrombotic actions, CVD risk factors, vascular reactivity, specific gene variants, congenital heart diseases, migraine attack frequency, migrainespecific treatment and pathophysiological involvements of the migraine [5,9,[14][15][16]. Major prospective studies evaluated CVD risk factors in large number of migraineurs and non-migraineurs [10,13,17,23].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is associated with stroke and cardiovascular disease (CVD) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Potential mechanisms of increased risk for ischemic stroke and CVD have been postulated in migraineurs [5,9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is a greater risk of ischemic stroke (relative risk, 4.8) among cigarette-smoking women with a cigarette-smoking spouse vs those with a nonsmoking spouse. Finally, smoking modifies the influence of oral contraceptives on stroke risk, as there seems to be a 7-fold rise in risk among persons who both smoke and use oral contraceptives [38].…”
Section: Modifiable Lifestyle Risk Factorsmentioning
confidence: 99%
“…3 Ischemic stroke is more common in women with than without migraine, 4,5 and risk is increased in those taking oral contraceptives. 6 There is a striking increase in frequency of pregnancy-associated stroke in women with a history of migraine, although the absolute level of that risk is low. 7 Migraine is associated with pre-eclampsia, [8][9][10][11] itself a marker of risk for later ischemic stroke 12 Other disorders influenced by migraine history include endometriosis and metrorrhagia.…”
Section: Introductionmentioning
confidence: 99%